2011
DOI: 10.3109/10715762.2011.571683
|View full text |Cite
|
Sign up to set email alerts
|

3,3′-Diindolylmethane but not indole-3-carbinol activates Nrf2 and induces Nrf2 target gene expression in cultured murine fibroblasts

Abstract: There is increasing interest in the gene-regulatory activity of Brassica vegetable derived phytochemicals such as 3,3'-diindolylmethane (DIM) and indole-3-carbinol (I3C). DIM is formed under acidic conditions by dimerization of I3C. This study compared the Nrf2 activating potential of DIM and I3C in murine fibroblasts (NIH3T3). In contrast to its precursor I3C, DIM induces the transactivation of Nrf2. Furthermore, Nrf2 targets such as HO-1, γGCS and NQO1 were increased on the mRNA and protein levels following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Diehn et al reported that enhanced ROS scavenger results in low ROS levels, and tumor radio-resistance (45). GCLC, HO-1 and NQO1 are Nrf2-regulated genes and protect against oxidative and xenobiotic stress by mopping up ROS (46)(47)(48)(49). In our study, inhibition of Nrf2 significantly attenuated IR-induced Nrf2 nuclear translocation and decreased GCLC, HO-1 and NQO1 expression after irradiation.…”
Section: Discussionsupporting
confidence: 64%
“…Diehn et al reported that enhanced ROS scavenger results in low ROS levels, and tumor radio-resistance (45). GCLC, HO-1 and NQO1 are Nrf2-regulated genes and protect against oxidative and xenobiotic stress by mopping up ROS (46)(47)(48)(49). In our study, inhibition of Nrf2 significantly attenuated IR-induced Nrf2 nuclear translocation and decreased GCLC, HO-1 and NQO1 expression after irradiation.…”
Section: Discussionsupporting
confidence: 64%
“…Resent studies shown that DIM induces the transactivation of Nrf2 in cultured murine fibroblasts [19], while AMPKα2 regulates expression of estrogen-related receptor-alpha (ERRα, a transcriptional factor often affects mitochondrial antioxidants and energy metabolism) [20]. Thus, we detect the myocardial oxidative stress markers and expression of NRF2 and ERRα etc after DIM-treated in both wild type and AMPKα2 KO mice.…”
Section: Resultsmentioning
confidence: 86%
“…Recent research has suggested DIM induced Nrf2 transactivation [19], which is a protective regulator that prevents the maladaptive cardiac remodeling and heart failure associated with a sustained pathological hemodynamic stress via at least partly the suppressing of oxidative stress [32]. Loss of Nrf2 sensitizes cardiomyocytes and cardiac fibroblasts to oxidative stress-mediated cell death [34].…”
Section: Discussionmentioning
confidence: 99%
“…Natural Nrf2 activators are also found in the brassica plants. One of these compounds which increases the activity of Nrf2 and not causes toxic effects on NIH3T3 cells is 3,3-diindolylometan which is derived from indol-3-carbinol fermentation [ 20 ]. Walnut sprouts extracts also contain natural Nrf2 activators that cause an increase in cells resistance to oxidative stress and increase survival up to 50 % in the case of fibroblast cells exposed to UVB [ 13 ].…”
Section: Nrf2 Activators In Fibroblastsmentioning
confidence: 99%